Incidence and mortality trends of neglected tropical diseases and malaria in China and ASEAN countries from 1990 to 2019 and its association with the socio-demographic index - Qiao Liu; Wenxin Yan; Chenyuan Qin; Min Du; Yaping Wang; Min Liu; Jue Liu (BMC, 2023)
Abstract Background People in China and the countries in the Association of Southeast Asian Nations (ASEAN) are affected by neglected tropical diseases and malaria (NTDM). In this study, we aimed to assess the current status and trends of NTDM burden from 1990 to 2019 in China and ASEAN countries, and also explore the association of NTDM burden with socio-demographic index (SDI). Methods The data from the Global Burden of Diseases Study 2019 (GBD 2019) results were used. Absolute incidence and death number, and age-standardized incidence and mortality rate (ASIR and ASMR) of NTDM in China and ASEAN were extracted. The estimated annual percentage change (EAPC) and join-point regression in the rates quantified the trends. Nonlinear regression (second order polynomial) was used to explore the association between SDI and ASRs. Results The ASIR of NTDM increased in China, Philippines, Singapore and Brunei, at a speed of an average 4.15% (95% CI 3.83-4.47%), 2.15% (1.68-2.63%), 1.03% (0.63-1.43%), and 0.88% (0.60-1.17%) per year. Uptrends of ASIR of NTDM in recent years were found in China (2014-2017, APC = 10.4%), Laos (2005-2013, APC = 3.9%), Malaysia (2010-2015, APC = 4.3%), Philippines (2015-2019, APC = 4.2%), Thailand (2015-2019, APC = 2.4%), and Vietnam (2014-2017, APC = 3.2%, all P < 0.05). Children < 5 had relatively low incidences but unexpectedly high mortality rates of NTDM in most ASEAN countries. Both incidence and mortality rates of NTDM were higher in older people. ASIR and ASMR of NTDM had a U-shaped association with SDI. Conclusions The burden of NTDM in China and ASEAN countries was still huge and affects vulnerable and impoverished populations' livelihoods, including children under the age of 5 and people aged 60 and older. Facing with the large burden and complex situation of NTDM in China and ASEAN countries, regional cooperating strategies are needed to reduce the burden of NTDM, so as to achieve the goal of elimination in the world.